The Impact of Enhancing the Damping in Lead Rubber Bearings on the Seismic Behavior of Base-isolated Steel Buildings - Athamnia, Brahim; Kaab, Mohamed Zohaïr; Boufarh, Rafik (Engineering, Technology & Applied Science Research, 2024)
This study investigates the seismic behavior of a five-story steel base-isolated building equipped with Lead Rubber Bearings (LRBs). Focus is given to enhancing the damping of LRBs, from 10% to 30%, and its impact on seismic response. We specifically examine the story drift and acceleration under seismic excitations applied through 21 different time histories. The findings reveal that increasing the LRB damping to a range of 15-20% significantly improves the seismic performance of the building, effectively reducing both story drift and acceleration. These results underscore the importance of optimal damping levels in LRBs for enhancing the seismic resilience of base-isolated structures.